2023
DOI: 10.3389/fgene.2023.1142326
|View full text |Cite
|
Sign up to set email alerts
|

Developing a non-invasive diagnostic model for pediatric Crohn’s disease using RNA-seq analysis

Abstract: Introduction: Pediatric Crohn’s disease is a chronic inflammatory condition that affects the digestive system in children and adolescents. It is characterized by symptoms such as abdominal pain, diarrhea, weight loss, and malnutrition, and can also cause complications like growth delays and delayed puberty. However, diagnosing pediatric Crohn’s disease can be difficult, especially when it comes to non-invasive methods.Methods: In this study, we developed a diagnostic model using RNA-seq to analyze gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Since the most of RNA-seq data involved in the other six TWAS were either not associated with CD or did not include appropriate cases and controls (HC only, CD only, CD and UC), we found another two well-designed studies for comparison. Two Asina studies identified differentially expressed genes by RNA-seq in CD patients [ 154 , 155 ]. Unfortunately, there was no susceptibility gene overlap between RNA-seq results and TWAS results neither in the ileum or colon.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Since the most of RNA-seq data involved in the other six TWAS were either not associated with CD or did not include appropriate cases and controls (HC only, CD only, CD and UC), we found another two well-designed studies for comparison. Two Asina studies identified differentially expressed genes by RNA-seq in CD patients [ 154 , 155 ]. Unfortunately, there was no susceptibility gene overlap between RNA-seq results and TWAS results neither in the ileum or colon.…”
Section: Future Perspectivesmentioning
confidence: 99%